Prioritizing limb loading improves symmetry during dual-tasking in individuals following anterior cruciate ligament reconstruction - Chan, Ming-Sheng; Sigward, Susan (Frontiers in Sports and Active Living, 2023)
Understanding the extent to which attention prioritization interfere with limb loading in daily activities following anterior cruciate ligament reconstruction (ACLr) is important for reshaping loading behaviors. A dual-task paradigm, prioritizing limb loading symmetry (LLS) during standing or response time during an upper extremity task response time task was used to probe the effects of attention prioritization of loading. Individuals 115.6 ± 17.8 days post-ACLr (ACLr; n = 13) and matched healthy individuals (n = 13; CTRL) performed a simple response time (RT) task and 2 dual tasks prioritizing limb loading (LS-RT) and response time (RT-LS). 2 × 3 General Linear Model repeated measures analyses determined effects of group and focus condition on LLS error and response time. Significant interaction (P = 0.010) was noted in LLS error. ACLr group, exhibited greater LLS error in RT (P = 0.001) and RT-LS (P = 0.001) than LS-RT condition. ACLr group exhibited greater LLS error in the RT (P = 0.001) and RT-LS (P = 0.040) than CTRL, but not in LS-RT. A main effect of condition (P < 0.001) for response time indicated that times were slower in LS-RT compared to RT (P < 0.001) and to RT-LS (P < 0.001) for both groups. These data suggest that limb loading symmetry during standing is more automatic for controls than individuals following ACLr. Unlike controls, improving loading symmetry during standing requires additional attention in individuals in early recovery following ACLr.